2002
DOI: 10.1093/ajcn/75.3.587
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Durnin-Womersley formula to estimate change in subcutaneous fat content in HIV-infected subjects

Abstract: The Durnin-Womersley formula can be used to predict change in SAT. The limits of agreement and the SEE for predicting change in SAT by MRI are approximately twice as great as the error of repeated Durnin-Womersley measures in control subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…All measurements were performed twice, and the observers were supervised by a single trainer. The Durnin-Womersley formula was used to calculate the percentage of body fat (12), which was closely related to the amount of subcutaneous adipose tissue (13). …”
Section: Methodsmentioning
confidence: 99%
“…All measurements were performed twice, and the observers were supervised by a single trainer. The Durnin-Womersley formula was used to calculate the percentage of body fat (12), which was closely related to the amount of subcutaneous adipose tissue (13). …”
Section: Methodsmentioning
confidence: 99%
“…All patients received stable HAART throughout the study. The median duration of HIV-1 infection was 12.3 years, and the median number of prior antiretroviral treatments was 9 (range: [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. More than 50% of the patients received monotherapy with a nucleoside reverse transcriptase in- hibitor (NRTI) and more than 80% received dual NRTI therapy before starting HAART.…”
Section: Subjects and Safetymentioning
confidence: 99%
“…Furthermore, expensive and time-consuming three-dimensional imaging techniques such as computed tomography or magnetic resonance imaging (MRI) are needed to distinguish between simple adiposity and visceral fat accumulation and also to determine the effectiveness of any interventions undertaken. However, MRI provides a precise tool to measure fat and its distribution with an estimated measurement error as low as 1-6% for repeated reading and 2-10% for repeated scanning [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated their utility in HIV atrophy and other conditions. [2][3][4][5][6][7][8][9][10][11][12][13] However, studies of SAT structure remain scarce. 14 Moreover, the terms for describing adipose tissue have been subject to change.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging techniques such as magnetic resonance imaging (MRI) or computed tomography (CT) enable distinction between visceral and subcutaneous adipose tissue (SAT). Several studies have demonstrated their utility in HIV atrophy and other conditions 2–13 …”
mentioning
confidence: 99%